Preliminary Results of Magnetically Controlled Growing Rods for Early Onset Scoliosis. Issue 8 (December 2017) - Ridderbusch, Karsten; Rupprecht, Martin; Kunkel, Philip; Hagemann, Christian; Stücker, Ralf
Abstract : Background: Growth-sparing techniques for the treatment of early onset scoliosis (EOS) have developed significantly over the last years. Traditional growing rods (GRs) require repeated surgical lengthening under anesthesia. Since June 2011 we have been using the magnetically controlled growing rods (MCGR) to treat patients with progressive EOS. Methods: Thirty-five patients with EOS of different etiologies underwent treatment with MCGR. We record about our preliminary results of 24 patients who fulfilled the inclusion criteria of a minimum follow-up (FU) of 12 month and >3 lengthenings. The mean age at surgery was 8.9±2.5 years. Correction of the primary curve after the index surgery and after lengthenings was measured on standing radiographs using the Cobb technique. T1-T12 and T1-S1 spinal length were also measured. Intraoperative and postoperative complications were recorded. Results: The mean FU was 21.1±7.3 months. All patients had a minimum of 3 outpatient lengthenings [mean, 4.6±1.5 (range, 3 to 8)]. The mean primary curve was 63±15 degrees (range, 40 to 96 degrees) and improved to 29±11 degrees (range, 11 to 53 degrees; P <0.001) after MCGR. The mean major curve after most recent lengthening was 26 degrees (range, 8 to 60 degrees; P <0.07). The T1-T12 as well as the T1-S1 length increased significantly ( P <0.001). The mean preoperative thoracic kyphosis decreased from 43±24 degrees (range, −32 to 86 degrees) to 27±12 degrees (range, 9 to 50 degrees; P <0.001) after surgery, respectively, and measured 32±12 degrees (range, 12 to 64 degrees; P <0.05) at last FU. In 1 patient a loss of distraction occurred making rod exchange necessary. Three patients developed a proximal junctional kyphosis and in another patient a screw pull out occurred that required revision surgery. Conclusions: Our results demonstrate that MCGR is a safe and effective nonfusion technique in the treatment of progressive EOS avoiding repeated surgical lengthening procedures. It provides adequate distraction similar to standard GR. The magnetically induced transcutaneous lengthening allows noninvasive distraction achieving spinal growth comparable to conventional GR techniques. Level of Evidence: Level IV—retrospective nonrandomized objective study.